Development of a unique instructional paradigm for teaching English as a foreign language in Korea: an examination of its effectiveness - Kent, David Bradley (Curtin University, 2007)
The native language of South Korea has come to contain a linguistic subset consisting of English and European loanwords and pseudo-loanwords. The notion that the English as a Foreign Language (EFL) learner is immersed in such a lexicon, and that this terminology can be utilized to effectively assist target language (Standard American English) vocabulary acquisition by the false-beginner through Computer Assisted Language Learning (CALL), was evaluated and examined. The empirical investigation employed a within-methods (i.e. experiment and survey) design. To this end, the researcher developed and deployed multimedia-based learning environments to empirically test research suppositions. In particular, to examine how the student’s knowledge of English words adapted for use in the South Korean vernacular – loanwords – is affected by their attitudes towards computerized instruction, their preference for certain methods of learning and teaching, and also by the attributes of computerized instructional packages. Ultimately, a method of instruction grounded in both CALL and linguistic theory was developed and its effectiveness for use with South Korean EFL learners in a university English program setting assayed. Scholarly accounts of the South Korean cultural learning style were also taken into consideration, and the implications such accounts hold for the implementation of CALL initiatives scrutinized.The findings of this study are significant at the administrative, practitioner, and field level. Research outcomes indicate (a) computer use did not bias results obtained through CALL: (b) use of the L1 (first language) to assist foreign language acquisition produced positive learning gains, albeit marginal and limited, as evidenced by the persistent difficulty learners had in building new form-meaning connections between pseudo-loanwords in South Korean and English-equivalents; and, (c) multimedia-based learning developed on cultural and classroom expectations of learners, as found in the literature, was not as successful as that it was contrasted against. Consequently, results of the research come to support usability of CALL in the tertiary education sector, the existence of a ‘stabilized interlanguage’ on the South Korean peninsula and the need to re-profile the South Korean cultural learning style and student classroom expectations that pertain to EFL.